2D hierarchical lattices' imperfection sensitivity to missing bars defect. Issue 4 (July 2015) - Wang, Bo; Shi, Yunfeng; Li, Rui; Chen, Youwei; Mo, Yihua
Abstract: Commercially available lattices contain various kinds of morphological imperfections which result in great degradation in lattices' mechanical properties, therefore, to obtain imperfection insensitive lattice structure is obviously a practical research subject. Hierarchical structure materials were found to be a class of promising anti-defect materials. This paper builds hierarchical lattice by adding soft adhesion to lattice's cell edges and numerical results show that its imperfection sensitivity to missing bars is minor compared with the classic lattice. Soft adhesion with appropriate properties reinforce cell edge's bending stiffness and thus reduce the bending deformation in lattice caused by missing bars defect, which is confirmed by statistical analysis of normalized node displacements of imperfect lattices under hydrostatic compression and shear loads.